Design and Construction of a Four-Point Contactless Switch for Industrial Application. - Okello, Thomas (Kabale University, 2024)
This project report details the design and construction of a contactless switching system for controlling four loads using an APDS and RGB gesture sensor, along with an Arduino. The system employs a proximity-based sensor to detect hand movements and control the four corresponding loads. The Arduino Uno board processes the sensor data and manages the relays to switch the loads on and off. The system is designed to offer a safe and convenient method of controlling electrical loads without physical contact. The system's accuracy and reliability were assessed through testing and iteration, showing high accuracy and fast response times. This makes the system suitable for various applications such as home automation and industrial control. The project showcases an efficient and cost-effective solution for contactless switching.